Antileishmanial potential of alkaloids isolated from plants: an integrative review - Veiga, Andreza do Socorro Silva da (2020)
Leishmaniasis treatment is often carried out with drugs of high toxic potential and high cost, and satisfactory therapeutic response is not usually observed. In this context, searching for therapeutic alternatives is urgent. This study seeks to evaluate the antileishmanial potential of alkaloids from plants. The search for scientific papers occurred at Pubmed, CAPES Journal Portal (PPC), Virtual Health Library (VHL) and COCHRANE using the descriptors: alkaloid and antileishmanial. The inclusion criteria were studies about alkaloids isolated from plants and tested against Leishmania parasite. A total of 805 publications were found in Pubmed, 825 in PPC, 4 in VHL and none in COCRHANE. After reading the titles and abstracts, articles containing other biological evaluations (350), chemical studies such as docking and material characterizations (388), evaluation of extracts and fractions activities (406) which did not fit in this research or were in duplicate (377) were excluded. Acridone and all the naphthylisoquinolinic and tetrahydroisoquinolinic alkaloids were active or moderately active against Leishmania promastigotes or amastigotes, and indolizidine was active against both forms. The β-carbolines were inactive or moderately active against Leishmania promastigotes, with the exception of flavopereirine. The indolizidine alkaloid was the most promising as a future drug candidate, since it was very active against both forms of Leishmania.